Associations of rare nicotinic cholinergic receptor gene variants to nicotine and alcohol dependence. Issue 8 (30th July 2016) - Zuo, Lingjun; Tan, Yunlong; Li, Chiang‐Shan R.; Wang, Zhiren; Wang, Kesheng; Zhang, Xiangyang; Lin, Xiandong; Chen, Xiangning; Zhong, Chunlong; Wang, Xiaoping; Wang, Jijun; Lu, Lu; et al.
Abstract : Nicotine's rewarding effects are mediated through distinct subunits of nAChRs, encoded by different nicotinic cholinergic receptor ( CHRN ) genes and expressed in discrete regions in the brain. In the present study, we aimed to test the associations between rare variants at CHRN genes and nicotine dependence (ND), and alcohol dependence (AD). A total of 26, 498 subjects with nine different neuropsychiatric disorders in 15 independent cohorts, which were genotyped on Illumina, Affymetrix, or PERLEGEN microarray platforms, were analyzed. Associations between rare variants (minor allele frequency (MAF) <0.05) at CHRN genes and nicotine dependence, and alcohol dependence were tested. The mRNA expression of all Chrn genes in whole mouse brain and 10 specific brain areas was investigated. All CHRN genes except the muscle‐type CHRNB 1, including eight genomic regions containing 11 neuronal CHRN genes and three genomic regions containing four muscle‐type CHRN genes, were significantly associated with ND, and/or AD. All of these genes were expressed in the mouse brain. We conclude that CHRNs are associated with ND (mainly) and AD, supporting the hypothesis that the full catalog of ND/AD risk genes may contain most neuronal nAChRs‐encoding genes. © 2016 Wiley Periodicals, Inc.